Análise comparativa da eficiência de instrumentos rotatórios de niquel-titânio ProTaper NEXT e ProTaper Universal - Gustavo de Cristofaro Almeida (2016)
The NiTi instruments have geometrical and dimensional characteristics that could play an important hole in the cutting efficiency. Torque and apical force exerted during the root canal preparation are parameters that define this mechanical property. This study evaluated the apical force and torque required by the instruments ProTaper Universal (PTU) S2 and F1, and ProTaper NEXT (PTN) X1 and X2, with similar diameters and different geometries, to penetrate standardized acrylic blocks containing an artificial canal previously explored with rotary instruments Pathfile #13 and #16. The parameters were determined using a bench-testing machine, where the instruments were set to move against the artificial canal in a constant speed of 0.09 mm/sec. The X-Smart Plus motor, with a rotational speed of 300 rpm and torque limitation of 4N.cm, was employed to drive the instruments and the load cell of the machine recorded the apical force exerted, while a digital multimeter attached to the endodontic motor recorded the torque required during the work of the instrument along the canal. Ten instruments of each type were tested using a new acrylic block for each system, in a sequence of S2 and F1 for PTU, and X1 and X2 for PTN. The results showed that the instruments of the PTU system displayed lower torque and apical force during the test, when compared to PTN instruments.